Evaluación de concentraciones de gases y vapores generados en el expendio de combustible en la gasolinera del sindicato de choferes profesionales del cantón Saquisilí, provincia de Cotopaxi, periodo 2014 - 2015 - Batallas Changoluisa, Alex Paúl (2015)
The purpose of this research is to monitor gases and vapors emitted into the environment in the process to sale fuel and then this process is compared with Table No. 4 of Environmental Regulations for Hydrocarbon Operations in Ecuador (RAHOE), the investigation was made at the service station to Professional Drivers of Saquisilí canton located at Simon Bolivar in 0°50’33.6’’S y 78º39’50.6’’W. First, for making the investigation was necessary to find information about the gas station, some of them are the identification, limits to service station, characteristics of the place, infrastructure, operation, features of the areas, staff or workers to the service station andweather conditions....